2017
DOI: 10.1037/tam0000078
|View full text |Cite
|
Sign up to set email alerts
|

Case study: The Isla Vista campus community mass murder.

Abstract: A case study is presented of a 22-year-old student mass murderer who stabbed or shot to death 6 college students and wounded 14 others. Because he left a lengthy autobiographical "manifesto" and social media posts, and an extensive law enforcement investigation ensued, a significant amount of information exists to examine the case. The assailant presents a complex diagnostic and psychodynamic picture, including likely features of autism spectrum disorder, narcissism, psychopathy, and depression. A predominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 14 publications
2
48
0
Order By: Relevance
“…If police had looked closer into his case, they might have discovered that he exhibited many of the key warning signs outlined by Meloy et al (2012) and Lankford (2018). In turn, this could have justified further investigations that would have revealed he was acquiring weapons, building homemade explosives, and running surveillance on potential targets (O'Neill & Weisfeldt, 2015), all of which would warrant significant cause for concern when evaluated from a threat assessment perspective (Madfis, 2014b;O'Toole, 2000;White, 2017). This information could have been used to prevent his eventual attack.…”
Section: Lesson 3: Law Enforcement Needs To Be Educated and Trained Omentioning
confidence: 94%
See 1 more Smart Citation
“…If police had looked closer into his case, they might have discovered that he exhibited many of the key warning signs outlined by Meloy et al (2012) and Lankford (2018). In turn, this could have justified further investigations that would have revealed he was acquiring weapons, building homemade explosives, and running surveillance on potential targets (O'Neill & Weisfeldt, 2015), all of which would warrant significant cause for concern when evaluated from a threat assessment perspective (Madfis, 2014b;O'Toole, 2000;White, 2017). This information could have been used to prevent his eventual attack.…”
Section: Lesson 3: Law Enforcement Needs To Be Educated and Trained Omentioning
confidence: 94%
“…Previous research has found that leakage is quite common among similar offenders (Bondü & Scheithauer, 2010;Hempel, Meloy, & Richards, 1999;Leuschner et al, 2011;Madfis, 2014a;Meloy, Hempel, Mohandie, Shiva, & Gray, 2001;Meloy & O'Toole, 2011;Silver, Horgan, & Gill, 2018;Silver, Simons, & Craun, 2018;Vossekuil, Fein, Reddy, Borum, & Modzeleski, 2002;White, 2017). For instance, Hempel et al (1999) found that among 30 adult mass murderers who offended from 1949 to 1998, 67% made specific or general threats about their violent intentions.…”
Section: Leakage Of Mass Shooters' Violent Thoughts and Intentmentioning
confidence: 98%
“…The initial number of items was 78 -new, elaborated and drew up for this study-, which followed standards established for the construction of instruments (Cohen and Swerdlik, 2001; Kaplan and Saccuzzo, 2012). Said items were developed by answering the question: “What are the indicators present in predatory violence?” Based on the literature (Anderson and Bushman, 2002; Leary et al, 2003; Pollack et al, 2008; Declercq and Audenaert, 2011; Monuteaux et al, 2015; Bushman et al, 2016; Gerard et al, 2016; Freedman et al, 2017; Paradice, 2017; White, 2017), items on anger, appeal for weapons, resentment, taking justice into one’s own hands, suicidal ideation, substance abuse, bullying, and a sense of belonging in school, were generated. Content validity was obtained through a panel of evaluators that determined if items (e.g., “Having a weapon makes me feel more secure,” or “I have had feelings of revenge”) were essential to the construct of predatory violence.…”
Section: Methodsmentioning
confidence: 99%
“…In many ideologically motivated homicides, perpetrators in the Internet age have posted manifestos online prior to the commission of the offense. This was the case in the lone-actor terrorist killings in Oslo and Utøya, Norway, in 2011; the Isla Vista, CA rampage in 2014; the Charleston, SC, church shooting in 2015; the 2019 shootings in Christchurch, New Zealand, and El Paso, TX; and the murder of a federal judge's son by a misogynistic attorney in 2020, to name only a few (Arango et al, 2019;Barnes, 2012;Hamm & Ayers, 2021;Hong et al, 2020;Lankford, 2018;Lankford et al, 2019;Liem & Geelen, 2019;Tully, 2020;White, 2017). These manifestos may take the form of a written letter or essay, social media postings, or videos recorded and uploaded prior to the offense.…”
Section: Self-publishing and Media Sharingmentioning
confidence: 99%
“…Some of these subcultures revere lone‐actor terrorists, school shooters, and other perpetrators of mass homicides (Langman, 2018; Mackintosh et al., 2020). The mass shooting at a Wal‐Mart in El Paso, TX, in August 2019 is illustrative and bears notable similarities to other incidents of mass violence in recent years: (1) the shooter was male, (2) he was involved with extremist communities on the Internet, (3) he posted a manifesto online (in this case, to 8chan) prior to the incident, and (4) he was influenced by at least one previous mass shooting linked to Internet‐based hate (in this case, the mass shooting at a mosque in Christchurch, New Zealand, earlier that year) (ADL, 2020a; Marantz, 2019; Recupero & Rainey, 2021; Silver et al., 2018; White, 2017). Counterterrorism researchers have characterized the spread of white supremacist hate communities on the Internet and social media as an especially troubling development (Recupero & Rainey, 2021).…”
Section: Extremism and The Internetmentioning
confidence: 99%